2019
DOI: 10.12998/wjcc.v7.i3.382
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for routine coagulation monitoring with rivaroxaban: A case report and review of the literature

Abstract: BACKGROUNDRivaroxaban is a non-vitamin K antagonist oral anticoagulant that does not require coagulation monitoring based on current recommendations. Our goal is to explore whether routine coagulation monitoring should not be required for all patients receiving oral rivaroxaban, what relationship between routine coagulation abnormalities and bleeding, and how to deal with the above clinical situations through our case and review of the literature.CASE SUMMARYWe report a 67-year-old woman with a history of atri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…By contrast, Wu et al [7] reported a clinical case of a 67-year-old female with a normal kidney and liver function tests and normal platelet counts, who was treated with a normal dose of rivaroxaban for Pulmonary Embolism (PE) and bilateral intermuscular veins DVT. However, she developed rare abnormal prolongation coagulation tests of PT, aPPT, and gastrointestinal and gum bleeding after 24 hours of administration [7]. Current guidelines recommend that using DOAC, including rivaroxaban do not require coagulation monitoring, but a small number of patients may develop routine coagulation test changes and bleeding during rivaroxaban therapy, especially in the elderly [7].…”
Section: Rivaroxaban and Agementioning
confidence: 99%
See 4 more Smart Citations
“…By contrast, Wu et al [7] reported a clinical case of a 67-year-old female with a normal kidney and liver function tests and normal platelet counts, who was treated with a normal dose of rivaroxaban for Pulmonary Embolism (PE) and bilateral intermuscular veins DVT. However, she developed rare abnormal prolongation coagulation tests of PT, aPPT, and gastrointestinal and gum bleeding after 24 hours of administration [7]. Current guidelines recommend that using DOAC, including rivaroxaban do not require coagulation monitoring, but a small number of patients may develop routine coagulation test changes and bleeding during rivaroxaban therapy, especially in the elderly [7].…”
Section: Rivaroxaban and Agementioning
confidence: 99%
“…Rivaroxaban is approved with other DOACs such as apixaban and dabigatran in many countries in adult patients for thromboprophylaxis after elective hip or knee replacement surgery, prevention of stroke and systemic embolism with non-valvular atrial fibrillation (AF), for the treatment of Deep Vein Thrombosis (DVT) and Pulmonary Embolism (PE), and prevention of recurrent DVT and PE [5][6][7][8][9][10][11][12][13]. Prevention of stroke in AF was by far the most prevalent indication for prescribing a DOAC [14].…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations